m+8m+4m+6=

Simple and best practice solution for m+8m+4m+6= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m+8m+4m+6= equation:


Simplifying
m + 8m + 4m + 6 = 0

Reorder the terms:
6 + m + 8m + 4m = 0

Combine like terms: m + 8m = 9m
6 + 9m + 4m = 0

Combine like terms: 9m + 4m = 13m
6 + 13m = 0

Solving
6 + 13m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 13m = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 13m = 0 + -6
13m = 0 + -6

Combine like terms: 0 + -6 = -6
13m = -6

Divide each side by '13'.
m = -0.4615384615

Simplifying
m = -0.4615384615

See similar equations:

| 4w-7w=-9 | | 16x^2-8x+14=0 | | .4/x=2 | | h=-16x^2+6x+33 | | 11x-2=4x+12 | | .0525=0.006x+0.0045 | | -2.3-6z-5.3-3z=-8z+5.7 | | 6(c-6)=5(2+c) | | 860=2(2x-65)+2x | | 3b^3-18b=10b-49 | | -x^2+17x-5=0 | | 0.05d-0.2-17=13 | | 8(t-4)-6(4t+3)=-17(t+5)+7 | | x^3+2x^2=150 | | 6x-6-4x=26+x | | 0.35x-1.2=0.2 | | -2=5(x+9)-8x | | 6t-0=5+8b | | 5(x+0.8)=16 | | -5=16t^2+70t+4 | | 2x^2+(3k-1)x+(3k^2-1)=0 | | -9(w-8)-(4w-1)=-14w | | v-8=16 | | lne-2x=8 | | 2x^2+(3k-1)x(3k^2-1)=0 | | [(x-105)/5] | | 7z+7-3z=9+3z+1 | | 0.8(x-0.1)=1.2 | | [(x-105)/4] | | 2x^2-3+2=0 | | p+6=x-y | | -5(y+5)=-4y-5 |

Equations solver categories